192k views
0 votes
Factor 27a^3 b^9+8c^18

User Qfwfq
by
4.8k points

1 Answer

2 votes

For this case we must factor the following expression:


27a ^ 3b ^ 9 + 8c ^ 18

So, we rewrite the terms like:


27a ^ 3b ^ 9 = (3ab ^ 3) ^ 3\\8c ^ {18} = (2c ^ 6) ^ 3

So, we have:


(3ab ^ 3) ^ 3 + (2c^6) ^ 3 =

Being both perfect cube terms, we factorize by applying the cube sum formula:


(a ^ 3 + b ^ 3) = (a + b) (a ^ 2-ab + b ^ 2)

Where:


a = 3ab ^ 3\\b = 2c ^ 6\\(3ab ^ 3 + 2c ^ 6) ((3ab ^ 3) ^ 2- (3ab ^ 3) (2c ^ 6) + (2c ^ 6) ^ 2) =\\(3ab ^ 3 + 2c ^ 6) (9a^2b ^ 6-6ab ^ 3c ^ 6 + 4c ^ {12})

Answer:


(3ab ^ 3 + 2c ^ 6) (9a2b ^ 6-6ab ^ 3c ^ 6 + 4c ^ 12)

User Tatarinho
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.